Leflunomide induces apoptosis in fludarabine-resistant and clinically refractory CLL cells - Dietrich, Sascha; Giese, Thomas; Hess, Michael; Tretter, Theresa; Rieger, Michael; Hüllein, Jennifer; Zenz, Thorsten; Ho, Anthony Dick; Dreger, Peter; Luft, Thomas (Clinical cancer research, 2012)
Purpose: Environmental conditions in lymph node proliferation centers protect chronic lymphocytic leukemia (CLL) cells from apoptotic triggers. This situation can be mimicked by in vitro stimulation with CD40 ligand (CD40L) and interleukin 4 (IL-4). Our study investigates the impact of the drug leﬂunomide to overcome apoptosis resistance of CLL cells. Experimental Design: CLL cells were stimulated with CD40L and IL-4 and treated with ﬂudarabine and the leﬂunomide metabolite A771726. Results: Resistance to ﬂudarabine-mediated apoptosis was induced by CD40 activation alone stimulating high levels of BCL-XL and MCL1 protein expression. Apoptosis resistance was further enhanced by a complementary Janus-activated kinase (JAK)/STAT signal induced by IL-4. In contrast, CLL proliferation required both a CD40 and a JAK/STAT signal and could be completely blocked by pan-JAK inhibition. Leﬂunomide (A771726) antagonized CD40L/IL-4-induced proliferation at very low concentrations (3 mg/ mL) reported to inhibit dihydroorotate dehydrogenase. At a concentration of 10 mg/mL, A771726 additionally attenuated STAT3/6 phosphorylation, whereas apoptosis of CD40L/IL-4-activated ("resistant") CLL cells was achieved with higher concentrations (IC50: 80 mg/mL). Apoptosis was also effectively induced by A771726 in clinically refractory CLL cells with and without a defective p53 pathway. Induction of apoptosis involved inhibition of NF-kB activity and loss of BCL-XL and MCL1 expression. In combination with ﬂudarabine, A771726 synergistically induced apoptosis (IC50: 56 mg/mL). Conclusion: We thus show that A771726 overcomes CD40L/IL-4-mediated resistance to ﬂudarabine in CLL cells of untreated as well as clinically refractory CLL cells. We present a possible novel therapeutic principle for attacking chemoresistant CLL cells. Clin Cancer Res; 18(2); 417-31. Ó2011 AACR.